2021
DOI: 10.1515/jelf-2021-2053
|View full text |Cite
|
Sign up to set email alerts
|

The influence of context on language alternation practices in English as a lingua franca

Abstract: This paper scrutinizes language alternation practices in different settings where English is predominantly used as the lingua franca (ELF). Data from different interactional contexts are examined: academic interactions from the ELFA corpus, doctoral defense discussions (also from the ELFA corpus), and informal family interactions. Corpus, discourse and conversation analytic methods and ethnographic information are used in analyzing these spoken data. I argue that translanguaging in lingua franca contexts is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As ELF users exploit multiple linguistic and cultural resources, linguistic practices function as markers of linguacultural identities (Wang, 2012) and across-cultural complex identities such as transcultural identities (Marotta, 2014). The views of language variants as codes relevant to speech communities, neatly defined cultural groups and fixed identities are irrelevant to global citizens (Bukhari, 2019;Pietikainen, 2021).…”
Section: Elf Linguistic and Cultural Diversitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As ELF users exploit multiple linguistic and cultural resources, linguistic practices function as markers of linguacultural identities (Wang, 2012) and across-cultural complex identities such as transcultural identities (Marotta, 2014). The views of language variants as codes relevant to speech communities, neatly defined cultural groups and fixed identities are irrelevant to global citizens (Bukhari, 2019;Pietikainen, 2021).…”
Section: Elf Linguistic and Cultural Diversitiesmentioning
confidence: 99%
“…Pitzl (2018) points out that the "Multiple Resource Pool" of a group of ELF users "is bound to vary considerably from context to context and will often only be discovered gradually by participants throughout an interaction" (p. 34). Pietikainen (2021) analysed language alternation practices in different ELF contexts. Her findings revealed that ELF practices are not only affected by users' repertoires but also by a complex web of individual, interpersonal, group-related and discourse environmental aspects.…”
Section: Elf Functional and Contextual Diversitiesmentioning
confidence: 99%